(untitled) (World Bulletin of Management and Law, 2024)
This article covers the objective legal framework of the concepts of the lawyer – as a contractual (voluntary) representative, the lawyer’s activity in preparing to take a vote of confidence and attend court as a representative, the participation of a lawyer at the stage of initiating a case and preparing a court hearing,the participation of a lawyer in proceedings .